2014
DOI: 10.1111/pim.12159
|View full text |Cite
|
Sign up to set email alerts
|

Echinostoma caproni (Trematoda): differential in vivo mucin expression and glycosylation in high‐ and low‐compatible hosts

Abstract: Enhanced mucus production and release appears to be a common mechanism for the clearance of intestinal helminths, and this expulsion is normally mediated by Th2-type immune responses. To investigate the factors determining the expulsion of intestinal helminths, we have analysed in vivo expression of mucin genes at the site of infection in two host species displaying different compatibility with Echinostoma caproni (Trematoda). Surprisingly, a general down-regulation on mucin mRNA expression was detected in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…Our results indicate that partial and complete resistance to E. caproni infections are associated with goblet cell hyperplasia and changes in mucus glycosylation at the time of challenge infection. Although previous studies have suggested that goblet cell hyperplasia has little effect on resistance to E. caproni infections 16 45 46 , our current results are somewhat confusing. Primary infection induced a goblet cell hyperplasia of about 4-fold greater than in negative controls from 4 wppi.…”
Section: Discussioncontrasting
confidence: 67%
“…Our results indicate that partial and complete resistance to E. caproni infections are associated with goblet cell hyperplasia and changes in mucus glycosylation at the time of challenge infection. Although previous studies have suggested that goblet cell hyperplasia has little effect on resistance to E. caproni infections 16 45 46 , our current results are somewhat confusing. Primary infection induced a goblet cell hyperplasia of about 4-fold greater than in negative controls from 4 wppi.…”
Section: Discussioncontrasting
confidence: 67%
“…), mice and rat intestine with Echinostoma caproni (Cortés et al . ), rat airway and small intestine with Nippostrongylus brasiliensis (Tsubokawa et al . ), lamb gut with Haemonchus contortus or Teladorsagia circumcincta (Hoang, Williams & Simpson ; Simpson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated electrogenic ion transport creates a driving force for water movement that can lubricate the epithelial surface and may assist in the expulsion of intestinal helminths: 82 water is important in the physical properties of mucus. 83,84 Intestinal goblet cell hyperplasia is perhaps the most prominent gut characteristic of infection with gastrointestinal parasitic helminths 3,85 and increases in mucin production, type (e.g., Muc5a) and glycosylation can be critical components of the epithelial barrier that aids the expulsion of helminths, such as the nematode N. brasiliensis [86][87][88][89] and the trematode, Echinostoma caproni; 90 indeed, helminths in their own defense may release proteases to degrade mucus. 91 The advent of mucin-gene knockout mice positions the field to unequivocally test the role of mucus in the expulsion of a range of parasitic helminths.…”
Section: Helminth and Host-derived Factors Impact On Intestinal Barrimentioning
confidence: 99%